Pengaruh Intellectual Capital, Kebijakan Keuangan, dan Kinerja Keuangan terhadap Nilai Perusahaan (TOBIN’S Q) (Studi pada Perusahaan Jasa yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2017-2019) - Jumiari, Ni Kadek Virgiani; Julianto, I Putu (Jurnal Ilmiah Akuntansi dan Humanika, 2020)
One of the objectives of establishing a company is to be able to increase the value of the company. Firm value affects a lot, in this study intends to examine the effect of intellectual capital, financial policy and financial performance on firm value. The subject of this research is the entire service companies on the Indonesia Stock Exchange (IDX) for the 2017-2019 period, amounting to 54 companies. The research sample was selected by 18 companies with purposive sampling technique. The data collection of this research is the method of documentation and study of literature. Data were analyzed with descriptive statistical tests and multiple linear regression analysis. The test results, namely, IC, DER, DPR, CR, ROE, DR, TATO and DY variables on company value are simultaneously influential, while DER, CR and DR on company value are partially affected, the rest are IC, DPR, ROE, TATO and DY individually have no effect on firm value.